2011
DOI: 10.1002/smll.201100915
|View full text |Cite
|
Sign up to set email alerts
|

Large Array of Sub‐10‐nm Single‐Grain Au Nanodots for use in Nanotechnology

Abstract: A uniform array of single-grain Au nanodots, as small as 5-8 nm, can be formed on silicon using e-beam lithography. The as-fabricated nanodots are amorphous, and thermal annealing converts them to pure Au single crystals covered with a thin SiO(2) layer. These findings are based on physical measurements, such as atomic force microscopy (AFM), atomic-resolution scanning transmission electron microscopy, and chemical techniques using energy dispersive X-ray spectroscopy. A self-assembled organic monolayer is gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 26 publications
2
71
0
Order By: Relevance
“…Once the best conditions have been determined on commercially available substrates, POM layers have been prepared onto template-stripped Au surfaces ( TS Au) 85 and Au nanodots [86][87] tetrahedra green) and schematization (not at scale) of its electrostatic deposition onto a 8-amino-1octanethiol (AOT) SAM. The POM has a wheel-shaped structure with a diameter of ~2.0 nm and a thickness of ~1.0 nm.…”
Section: Deposition Of [H 7 P 8 W 48 O 184 ] 33onto 8-amino-1-octanetmentioning
confidence: 99%
“…Once the best conditions have been determined on commercially available substrates, POM layers have been prepared onto template-stripped Au surfaces ( TS Au) 85 and Au nanodots [86][87] tetrahedra green) and schematization (not at scale) of its electrostatic deposition onto a 8-amino-1octanethiol (AOT) SAM. The POM has a wheel-shaped structure with a diameter of ~2.0 nm and a thickness of ~1.0 nm.…”
Section: Deposition Of [H 7 P 8 W 48 O 184 ] 33onto 8-amino-1-octanetmentioning
confidence: 99%
“…Typically, in a few μm 2 C‐AFM image (Figure c), 2000–4000 NMJs are measured in a single scan. Current or conductance histograms are simply extracted from these C‐AFM images and repeating this approach at various bias allow the measurement of 2D histograms of the current‐voltages (I−V) curves . With this NMJ approach, focusing on the archetype alkylthiol junctions, it was observed that the number of the conductance peaks depends on the atomic details of the electrode surface: 2 peaks for NMJs on single crystal Au nanodot vs. 3 peaks for SAMs on more disordered polycrystalline Au surfaces .…”
Section: Nanodot Molecular Junctionsmentioning
confidence: 99%
“…Periodic arrays of nanometre-sized metal structures hold great promise for future applications, e.g., in nanoelectronics [14] or in biohybrid devices [56]. The most common technique to generate such structures is the evaporation of a thin metal film through a resist mask structured by electron beam lithography (EBL) or other lithographic techniques [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…The most common technique to generate such structures is the evaporation of a thin metal film through a resist mask structured by electron beam lithography (EBL) or other lithographic techniques [1,7]. In general, these fabrication techniques involve five or more processing steps, including formation, patterning and development of resist films, metal evaporation/sputtering and lift-off, whereby feature sizes rarely go beyond the 10 nm threshold [1]. Depending on the chosen substrate, e.g., SiO 2 , additional metal layers such as Ti are needed as adhesive layers.…”
Section: Introductionmentioning
confidence: 99%